PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (PERSPEKTIF UU PKDRT DAN UU PERLINDUNGAN ANAK) - Ahmad Yunus (Pusat Riset dan Inovasi Nasional, 2021)
Every child has human rights, like the rights of adults, not many parties are involved in thinking and willing to take concrete steps to protect children's rights. Children are immature individuals, both physically and mentally, let alone socially. So that when compared to adults, it is clear that children will be more at risk of violence and neglect. Children can become victims of violence anytime and anywhere, including within their own families or in other words, children become victims of domestic violence. Whereas the family should be the safest and most comfortable place for children, comfortable and safe in terms of physical and psychological. In this case the state must really be present and provide protection for children, where children are the next generation of the Nation and State of Indonesia. If the safety and comfort of every Indonesian child is guaranteed, then this nation will have a good and superior generation so that it can make Indonesia a better country as a whole.